2007
DOI: 10.1111/j.1600-0420.2007.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of travoprost, latanoprost and bimatoprost on ocular circulation: a 6‐month clinical trial

Abstract: ABSTRACT.Purpose: To study the effect of three prostaglandin F 2 -a (PG) analogues on retrobulbar blood flow velocity in previously untreated patients with primary open-angle glaucoma (POAG) or ocular hypertension (OHT), using colour Doppler ultrasound. Methods: Sixty newly diagnosed patients with POAG or OHT were randomly assigned to travoprost 0.004% (n ¼ 12 with POAG, n ¼ 8 with OHT), latanoprost 0.005% (n ¼ 11 with POAG, n ¼ 9 with OHT) and bimatoprost 0.03% (n ¼ 13 with POAG, n ¼ 7 with OHT) treatment gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 30 publications
2
36
0
2
Order By: Relevance
“…Figure 1 presents details of the exclusion criteria at the various stages during the study selection process. Five trials had more than 2 intervention arms, 28 [28][29][30][31][32][39][40][41] We did not pool the data from one trial, reported as an abstract, as we were unable to determine the group sizes. 42 Table 1 and 2 report the study characteristics and quality (see Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 presents details of the exclusion criteria at the various stages during the study selection process. Five trials had more than 2 intervention arms, 28 [28][29][30][31][32][39][40][41] We did not pool the data from one trial, reported as an abstract, as we were unable to determine the group sizes. 42 Table 1 and 2 report the study characteristics and quality (see Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27] Among the topical antiglaucoma eye drops, the prostaglandin F2-alpha analogs (travoprost, latanoprost, and bimatoprost) and dorzolamide increase OPP, whereas timolol, a beta-blocker, and brimonidine do not. [28][29][30] Therefore, to investigate the effect of eye drops, both the reduction in IOP and the hemodynamic effects of the medication should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…55 A randomized double-masked crossover study 56 found a more favorable effect on ocular perfusion pressures (OPP) (which are directly related to OBF) with latanoprost than timolol. 56 Using color Doppler ultrasound, Koz et al 57 demonstrated that latanoprost, travoprost and bimatoprost increased blood flow velocity and OPP, and latanoprost and travoprost decreased the resistive index of the ophthalmic artery and central retinal artery (CRA). Alagoz et al 58 found increased CRA blood flow with bimatoprost and travoprost use.…”
Section: Other Effectsmentioning
confidence: 99%
“…68 Several meta-analyses [88][89][90][91] have directly compared the clinical efficacy of the three main PGAs, latanoprost, travoprost, and bimatoprost. Two independent meta-analyses, one 88 of 8 63,64,68,78,[85][86][87]92 and the other 89 of 13 trials (including double-blind parallel 57,63,93 or cross-over studies 41,42 and single blind parallel 64,78,85,86,[94][95][96] or cross-over studies) 97 found bimatoprost was superior to latanoprost in lowering morning IOP at all time points, supported by a later posthoc meta-analysis of 2 independent trials with 6 months follow-up. Weighted mean difference (WMD) for %IOP reduction (%IOPR) was 2.59% (P = 0.004) at 1 month to 5.60% (P , 0.001) at 6 months for one meta-analysis 89 and weighted mean (WM) IOP change from baseline ranged from a minimum of 0.50 mmHg (P = 0.05) at 0800 hours to a maximum of 1.17 mmHg (P , 0.001) at 1200 hours in the other meta-analysis 88 favoring bimatoprost over latanoprost.…”
mentioning
confidence: 99%
See 1 more Smart Citation